Răspunsuri la întrebare
Răspuns de
1
[tex] \int\limits { e^{arcsin(x) } } \, dx
u \rightarrow e^{arcsin(x)} \rightarrow dx = \sqrt{1-x^2} du
sin^2(x)= 1 - cos^2 (x)
x^2 = sin^2(u)
\int e^u cos(u) du
f= cos(u); f'= -sin(u)
g= e^u ; g'= e^u
= \mathrm{e}^u\cos\left(u\right)-\left(-\mathrm{e}^u\sin\left(u\right)-{\displaystyle\int}-\mathrm{e}^u\cos\left(u\right)\,\mathrm{d}u\right)
=\dfrac{\mathrm{e}^u\sin\left(u\right)+\mathrm{e}^u\cos\left(u\right)}{2}
[/tex]
[tex]=\dfrac{\sqrt{1-x^2}\mathrm{e}^{\arcsin\left(x\right)}+x\mathrm{e}^{\arcsin\left(x\right)}}{2}+C Simplificat/rescris: \dfrac{\left(\sqrt{1-x^2}+x\right)\mathrm{e}^{\arcsin\left(x\right)}}{2}+C[/tex]
[tex] Aici \dfrac{\mathrm{e}^u\sin\left(u\right)+\mathrm{e}^u\cos\left(u\right)}{2} Uitam de vechea substitutie u= arcsin(x) Folosim: sin(arcsin(x))=x si cos(arcsin(x))= \sqrt{1-x^2} [/tex]
[tex]=\dfrac{\sqrt{1-x^2}\mathrm{e}^{\arcsin\left(x\right)}+x\mathrm{e}^{\arcsin\left(x\right)}}{2}+C Simplificat/rescris: \dfrac{\left(\sqrt{1-x^2}+x\right)\mathrm{e}^{\arcsin\left(x\right)}}{2}+C[/tex]
[tex] Aici \dfrac{\mathrm{e}^u\sin\left(u\right)+\mathrm{e}^u\cos\left(u\right)}{2} Uitam de vechea substitutie u= arcsin(x) Folosim: sin(arcsin(x))=x si cos(arcsin(x))= \sqrt{1-x^2} [/tex]
Alte întrebări interesante
Engleza,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă